Answer:
The result of the expression a - (cd * b) with the given values is -75.
Step-by-step explanation:
The expression you provided is a - (cd * b). Given the values a = 5, c = 10, d = -2, and b = -4, we can substitute these values into the expression:
a - (cd * b) = 5 - ((10 * -2) * -4)
Solving the expression inside the parentheses first (according to the order of operations, or BIDMAS/BODMAS/PEDMAS), we get:
= 5 - ((-20) * -4) = 5 - 80 = -75
So, the result of the expression a - (cd * b) with the given values is -75.
I hope this helps! :)